Enhancing Brand Loyalty by Increasing Experiential Value through Customer Satisfaction in Boka Buka Restaurant Pondok Indah Mall - Nathania Gunawan; Harjanto Prabowo; Annetta Gunawan (The Winners, 2015)
This research was conducted at Boka Buka Restaurant. Boka Buka Restaurant is a casual French dining restaurant in Pondok Indah Mall. The objectives of the research are to examine if the experiential value contributes to customer satisfaction in Boka Buka Restaurant and t examine if the experiential value and customer satisfaction contributes partially and simultaneously to brand loyalty in Boka Buka Restaurant. The methods of the research are Pearson Correlation and Path Analysis. The data is obtained from the questionnaires which are distributed to the customers at Boka Buka Restaurant to measure the level of the Experiential Value, Customer Satisfaction, and Brand Loyalty, using a Likert scale. From the analysis of the data, it obtains structural equation Y = 0.812X + 0.5839ε1 where Experiential Value contributes significantly to Customer Satisfaction of 65.9% and Z = 0.255X + 0.582Y + 0.5958ε2 where Experiential Value and Customer Satisfaction simultaneously contribute significantly to the Brand Loyalty of 64.5%.